Hubungan Tingkat Pengetahuan Deteksi Dini Kanker Payudara Terhadap Kepatuhan Pemeriksaan Payudara Sendiri (Sadari) Pada Remaja Putri Di MAN 2 Samarinda - Burhanto, Burhanto; Norwanda, Tri Putri Ayu (Bunda Edu-Midwifery Journal (BEMJ), 2024)
The aim of this study was to determine the relationship between the level of knowledge of early detection of breast cancer and compliance with breast self-examination in young women at MAN 2 Samarinda. The method used was quantitative with a cross-sectional approach and using the Chi Square test with a confidence level of 95% and alpha 5% (0.05). The results obtained were pValue equal to 0.000 less than α equal to 0.05, which means accepting the alternative hypothesis (Ha). The conclusion is that there is a relationship between the level of knowledge about early detection of breast cancer and compliance with breast self-examination (BSE) among young women at MAN 2 Samarinda